The Effect of Simultaneous and Sequential Performance Evaluations on Restricting the Formal Diversity of Design - Al-Kazzaz, Dhuha Abed al-gany; Aswad, Ayad Waleed (Iraqi Journal of Architecture and Planning, 2018)
Performance-based architectural design is an approach to consider building performance as a key element in its generation and formation. This trend has become possible due to the development of digital technologies which enabled the designer to simulate the building performance digitally in different areas of design such as constructional, environmental, etc. In this approach, the performance assessment is an essential facility in the derivation of architectural form. Previous studies showed different opinions about where, when and how to apply evaluation criteria. Consequently, the research problem has been identified as: there is no clear understanding of the effect of different methods of assessing performance criteria (simultaneous and sequential) on the formal diversity of design alternatives. Accordingly, the paper adopts a computerized design strategy based on specific performance criteria and using commercial CAD software to explore the impact of changing the sequence of performance criteria on the formal diversity of design alternatives. The results show that the best designs resulting from the simultaneous evaluation differ from those resulting from the sequential evaluation. In addition, designs resulting from the sequential evaluation process vary when the sequence of performance criteria adopted in the evaluation is changed.